Religion as Determinants of Male Child Parenting Among Married Adults in Kwara State - Sanni, Ramata Funsho; Lasisi, Adekola Kamil; Ahmed, Taiye Hassan (International Journal of Universal Education, 2024)
Parents' religious inclination has been reported as a major determinant of rearing children. The study examined religion and psychological well-being as determinants of male-child parenting in Kwara State, Nigeria. The research aims to investigate the influence of religion on male child parenting among married adults in Kwara Central and determine its contribution to this issue. Two corresponding research questions and hypotheses guide the study. A descriptive survey of correlation was used. The study was conducted among male-child parents in Kwara Central. The population under scrutiny in this research comprises all wedded adults in Kwara Central with a projected estimate of 965,000 (National Population Commission, 2018). The study involved 384 married adults with male children from three Local Government Areas in Kwara Central, selected using the Kredjcie and Morgan table, specifically from Ilorin West, Ilorin South, and Ilorin East LGAs. The research instrument was a self-designed “Religion as Determinants of Male Child Parenting Scale (RDMCPQ). Experts assessed The RDMCPQ for its content, construct, and content validity. Its reliability was established through pilot testing and Pearson Product Moment Correlation Coefficient Statistics (PPMS), with a reliability index of 0.86. The findings show that religion has no significant relationship with male child parenting (F.cal.=5.32, p>0.05). Based on the findings, religion only explains about 11.7% of male child parenting in Kwara Central. The study recommended that married adults emphasise religious practice, especially for their male children. This will assist in enhancing the moral development of the children.